A Study of Membrane Potentials of Nervous Cells (Neurons) and the Role of Sodium and Potassium Ions in Their Creation - Qaderi, Jawed; Popalzai, Raihana (Journal of Natural Sciences – Kabul University, 2022)
In this article, the membrane potential, which is the electrical potential difference between the two sides of the cell membrane, is discussed. This potential is created due to the concentration difference of anions and cations on both sides of the cell membrane. The difference in the concentration of ions on both sides of the cell membrane creates a voltage difference known as the membrane potential. The largest contribution to this potential is caused by Na+ and Cl- ions, which have a higher concentration outside the cell, and K+ ions, which are concentrated inside the cell. With the improvements in electrophysiology and the discovery of the electrical activity of neurons, it was found that neural messages are transmitted from these cells to the target muscle by action potential. In this article, the role of voltage in neuronal activity, the types of membrane potentials, how the potential is created in the membrane of neurons, and its importance in the transmission of neural messages are discussed.